Suicide among Doctors: A Silent Emergency? - Sandip Subedi (Journal of Universal College of Medical Sciences, 2025)
Doctors are borne with crucial responsibility of saving life from the moment a life is being born. These doctors who have been entrusted with the wellbeing of others are becoming the victims of suicide. Since last few years we have been frequently listening to the news of doctors committing suicide in Nepal. This suggests that, within the health care centers, where lives are saved and healing takes place, a silent emergency is unfolding. In the United States of America, an estimated 300 to 400 doctors die by suicide each year, a rate of 28 to 40 per 100,000 which is more than double that of general population. Though data pertaining to suicide among doctors in Nepal is not available, media reports indicate that there is a rising trend among doctors’ suicide. This rise in suicide among doctors requires immediate attention from the society and the country too. CONCLUSION Suicidal death of a doctor is not a personal/familial tragedy, It is a failure of the whole society and the health system of the country. Since doctors are gem of the society, they deserve even more care and compassion that they freely give to the society when needed. The reported increase in the number of doctors’ suicide should be understood as the silent emergency that needs immediate attention to prevent failure in the health system.